Involving Students in School-Home Cooperation - Vršnik Perše, Tina; Grafenauer Ekart, Živa (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
The paper discusses the importance of involving students in school-home cooperation and its impact on their responsibility, motivation and behaviour. Great emphasis is placed on the active involvement of students, as it contributes to a better understanding of learning objectives, more effective communication between teachers, parents and students, and greater success in achieving educational and behavioural goals. Particular attention is paid to children with special needs, where participation further promotes their independence and enables an inclusive attitude. Based on qualitative research, we conclude that students who participate in three-way conferences are more motivated and better able to monitor their progress. Despite the benefits, there are challenges in implementing such practices, as teachers and parents often doubt students’ ability to participate. On this basis, we propose to increase the systematic involvement of students in school-home cooperation and to provide additional education and training for educators and parents to promote students’ active participation.